Smooth criminals. Volume 2 - Smith, Kiwi; Lustgarten, Kurt (BOOM! Box, 2020)
When a bit of hacking goes wrong, geeky Brenda accidentally unfreezes Mia, a master cat burglar from the 1960s. The game is afoot, and if they can figure out how to put aside their differences and work together, they just might wind up with millions of dollars. When Mia Corsair, the greatest cat burglar the 1960s had ever seen, woke up in a new world of dial-up, zip-off cargo shorts, and Y2K, the only thing she wanted was to catch back up to where she<U+2019>d been in 1969: on the verge of her biggest heist ever, and with it, mere inches away from getting away with millions of dollars (and that was in 60s money, too), notoriety...and freedom. Luckily for Mia, the nerd who accidentally unfroze her, Brenda Ospina (Tech Support, City College), might just be able to help her blend in in this brave new world, not to mention Brenda<U+2019>s got modern, tech-savvy tricks up her sleeve to help pull off the heist of the new millenium!